Effects on the Physiochemical Properties of Stored Pomegranate Seeds by the Application of Aloe Vera Gel as Coating Agent - Pirzadeh, M.; Aminlari, M. (Engineering, Technology & Applied Science Research, 2019)
Pomegranate has drawn the attention of dieticians and medicinal chemists due to its bioactive components. Natural coatings increase the shelf life of such agriculture products and reduce the risks associated with the use of chemical preservatives. Hence, we examined the effects of aloe vera coating on the pomegranate fruit. Aloe vera gel coating was utilized in three proportions of 25%, 33%, and 50%, and its effects on the pomegranate seeds were compared with a control sample. Experiments including moisture reduction, weight loss, sugar content, sensory properties, antioxidant capacity, and microbial analysis were performed over a period of 4 weeks. Results revealed that the percentage of moisture reduction in 50% aloe vera coated sample was lower than in other groups, and the mildew and yeast in these samples were less than in the other groups. However, the 50% aloe vera gel showed the highest level of contamination, over time. Furthermore, the 50% aloe vera gel showed higher sugar content, and over time the amount of sugar reduction in the 50% aloe vera was lower. Additionally, the percentage of weight loss in samples coated with aloe vera was lower than the control group, and in the 50% aloe vera group it was less than in the other groups.